1997
DOI: 10.1093/ajcn/66.3.672
|View full text |Cite
|
Sign up to set email alerts
|

Are genetic determinants of weight gain modified by leisure-time physical activity? A prospective study of Finnish twins

Abstract: A large number of studies have shown that obesity is both under genetic control and influenced by several environmental factors, including energy expenditure and intake. Several studies in animals and humans have furthermore suggested that certain environmental factors, such as a high fat intake, may modify the expression of the genes responsible for weight gain. The present study examined whether physical activity, measured at the baseline examination in 1975, was likely to play a differential role in subsequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
56
2
3

Year Published

1998
1998
2012
2012

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(65 citation statements)
references
References 13 publications
4
56
2
3
Order By: Relevance
“…On the other hand, sex-specific genetic effects on BMI and weight change have been reported previously. 1,22,23 Studies of the night-eating syndrome and related conditions have found these conditions to be associated with psychopathology, 13,[24][25][26] and the difference in associations between men and women in the present study may reflect sex-specific differences in the psychopathology of the obese. It could be that night eating is promoting weight gain because of a positive imbalance in the energy regulation caused by excessive energy intake during night.…”
Section: Discussionmentioning
confidence: 44%
“…On the other hand, sex-specific genetic effects on BMI and weight change have been reported previously. 1,22,23 Studies of the night-eating syndrome and related conditions have found these conditions to be associated with psychopathology, 13,[24][25][26] and the difference in associations between men and women in the present study may reflect sex-specific differences in the psychopathology of the obese. It could be that night eating is promoting weight gain because of a positive imbalance in the energy regulation caused by excessive energy intake during night.…”
Section: Discussionmentioning
confidence: 44%
“…Heitmann et al 19 studied BMI change in relation to past physical activity and found that the genetic influence on BMI change in men was detected at medium and high physical activity levels only. However, genetic influences on weight change appear to be rather distinct from those on BMI.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is difficult to disentangle these effects and this question has therefore rarely been studied. Heitmann et al 19 demonstrated that although both genetic factors and physical activity played an independent role in weight changes, physical activity level modified the genetic effects on weight change in male twins. The researchers hypothesized that genes suppressing weight gain may be expressed only at high physical activity levels.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, obese subjects reported physical impairment and reduced mobility more often 50 , while only 10% of subjects in an obese group and 24.4% of subjects in a non-obese group selected a moderate or higher level as indicative of the intensity of their daily physical activity 51 . Genetic factors may modify the effects of physical activity on weight change and it has been suggested that a sedentary lifestyle may have an obesity-promoting effect in men with a genetic predisposition 52 . Although physical activity levels are highly variable across different countries, beliefs in their health benefits are associated with the desire for losing weight 53 and also with the idea of staying healthy, to be fit or to relieve stress.…”
Section: Discussionmentioning
confidence: 99%